Governance and school performance in Colombia: A subnational look from the new institutional economy (Encuentros, 2024)
The article examines from a contractual logic the problems of quality and equity of education in the Colombian educational system, within a subnational context. The study applies a mixed and sequential approach considering the transaction and its attributes as the basic unit of analysis. The findings suggest that more autonomous educational systems are associated with better performance and indicate that the risks of inequity in performance are greater when the organization mode of the educational system has greater autonomy.
Keywords: Gobernanza escolar; Resultado escolar; Autonomía escolar; Nueva Economía Institucional